IMPROVING GROSS MOTOR SKILLS THROUGH LARGE BALL THROWING AND CATCHING ACTIVITIES FOR CHILDREN AGED 5-6 AT AN-NABILA PRESCHOOL PONTANG DISTRICT - Ifat Fatmawati; Amat Hidayat; Ibnu Sina (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
The lack of ability and strength of children in using hand and finger skills to throw and catch the ball is due to the less than optimal use of learning methods that involve physical activity. Therefore, this study aims to determine the use of play activities using the demonstration method to improve children's gross motor skills. The type of research used is classroom action research which is carried out collaboratively together with teachers. The subjects of the study were 21 children in class B of PAUD AN-Nabila. Data collection techniques in this study used observation and documentation. The study was conducted in three cycles, in one cycle, five research actions were carried out. The results of the study stated that playing throwing and catching a ball with a demonstration method can improve children's gross motor skills and this can be seen from the increase in each cycle. The highest average class score obtained from the pre-cycle to cycle I increased by 18.85%. and cycle I to cycle II experienced an increase of 15.45%, then the average class score in cycle II reached 89.53%. Therefore, this study is considered successful because the increase in children's fine motor skills in cycle II meets the established success criteria of 71% agreed upon by researchers and colleagues